2013
DOI: 10.1007/s11886-013-0369-z
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy for Pediatric Dilated Cardiomyopathy

Abstract: Dilated cardiomyopathy is a serious and life-threatening disorder in children. It is the most common form of pediatric cardiomyopathy. Therapy for this condition has varied little over the last several decades and mortality continues to be high. Currently, children with dilated cardiomyopathy are treated with pharmacological agents and mechanical support, but most require heart transplantation and survival rates are not optimal. The lack of common treatment guidelines and inadequate survival rates after transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 54 publications
0
25
0
1
Order By: Relevance
“…This can be achieved by modulating T cell proliferation as well as by regulating the type and quantity of T cell secretions. At present, MSCs provide a promising option (Selem et al, 2013) in the treatment of dilated cardiomyopathy. In rats with myocardial infarctions, it has been shown that the earlier the MSC transplantation was performed, the better the recovery of heart function was.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by modulating T cell proliferation as well as by regulating the type and quantity of T cell secretions. At present, MSCs provide a promising option (Selem et al, 2013) in the treatment of dilated cardiomyopathy. In rats with myocardial infarctions, it has been shown that the earlier the MSC transplantation was performed, the better the recovery of heart function was.…”
Section: Discussionmentioning
confidence: 99%
“…A well-studied type of stem cells consists of bone marrow-derived mesenchymal stem cells (MSCs), an undifferentiated population of cells capable of multipotent differentiation. Transplanted MSCs functionally recover acute and chronic ischemic myocardium in preclinical models of myocardial infarction, despite their limited engraftment in the injured myocardium (33). The precise mechanism of action has yet to be defined, but it may involve secretion of paracrine factors and stimulation of endogenous mechanisms of myocardial repair (3).…”
Section: We Demonstrate For the First Time That Intramyocardial Injecmentioning
confidence: 99%
“…Among these 5 patients, 3 did not make it to the transplant. 60,61 Further studies are necessary to establish their role.…”
Section: E) New Therapiesmentioning
confidence: 99%